Typology and ownership of rural open spaces in semi-arid regions: a case of Katsina State, Nigeria - Muhammad, Gidado Usman; Maulan, Suhardi; Mohd Yusof, Mohd Johari; Ibrahim, Roziya (Universiti Putra Malaysia, 2022)
Open spaces are an important feature of any neighborhood since they serve as a hub for the community’s socio-cultural activities. According to the National Population Commission, 64% of the population in northern Nigeria lives in rural areas and utilizes outdoor spaces for their socio-cultural lives. The typology and ownership of rural open spaces in north-western Nigeria have become major concerns for their impact on its management. This research explores the typology and ownership of open space in rural areas within north-western Nigeria to adduce the challenges facing its role in sustaining the communities’ cultural values. Observation from five communities in the Batagarawa local government. The study discovered a subconscious classification of rural open spaces into the community and private open spaces, each with defined boundaries, and the study also identified relevant stakeholders. As a result, the study suggests that the government play a coordinating role in resolving any disagreements among stakeholders so that open spaces can be better identified and the cultural values of these open spaces can be preserved, and thus concludes that open space typology and ownership have become a critical concern in sustaining the roles of open spaces in northern Nigeria’s semi-arid region.